Surgical Management of Neuroendocrine Tumors of the Appendix in Children and Adolescents: A Retrospective French Multicenter Study of 114 Cases. Issue 4 (10th December 2015) - de Lambert, Guénolée; Lardy, Hubert; Martelli, Hélène; Orbach, Daniel; Gauthier, Frédéric; Guérin, Florent
Abstract : Background: Right hemicolectomy (RHC) in patients with neuroendocrine tumors (NET) of the appendix has been advocated for tumors more than 2 cm, or with mesoappendix/vessel invasion, or with raised mitotic activity. No study demonstrated prolonged survival with RHC over appendectomy alone. The aim of this study was to contribute to define guidelines for secondary surgery in children or adolescents with NET of the appendix. Procedure: We contacted all French pediatric surgeons and oncologists by mail, and reviewed the records of patients under 18 with NET of the appendix from 1988 until 2012. Results: A total of 114 patients were recorded with a female/male ratio of 1.6. Median age at presentation was 12 years (range: 5–17 years). Ten patients had a tumor more than 2 cm. Twenty patients had evidence of extension into the mesoappendix, including five with blood or lymph vessels' invasion. Solely, one patient had a tumor with a high proliferative index. Incomplete resection was observed in three cases. Eighty‐five patients had no criterion for secondary surgery. Twenty‐nine patients had criteria for RHC but only 10 underwent surgery. None of the resected specimens showed carcinoid tumor. Three patients had positive lymph nodes. At the last follow‐up, all patients were alive and disease free. Conclusion: Appendectomy alone seems to be curative of these tumors with no influence on life expectancy. Follow‐up is not only unnecessary, but its means, whether clinical, radiological or biological, are ineffective.